Evaluation of a rapid immunochromatographic card test for Plasmodium falciparum in Ibadan, Nigeria (2001)
This short report describes the results of a rapid; simple and cost effective immunodiagnostic test for malaria in Ibadan, Nigeria. A total of 77% patients presenting at the children outpatient clinic, University College Hospital with malaria symptoms were screened for malaria parasites by microscopy using Giemsa stain and by the immunochromatographic card test. The immunodiagnostic test had a sensitivity of 93.1 % and a specificity of 95.8%, making a good alternative for malaria diagnosis especially in rural areas without electricity, where microscopy is not possible, and a decision is to be made on when to start treatment.